Healthcare providers' understanding of HIV serodiscordance in South Africa and Uganda: implications for HIV prevention in sub-Saharan Africa. Issue 2 (3rd April 2018) - Greener, Ross; Milford, Cecilia; Bajunirwe, Francis; Mosery, Faith N; Ng, Claudia K; Rifkin, Rachel; Kastner, Jasmine; Pillay, Lavanya; Kaida, Angela; Bangsberg, David R; Smit, Jennifer A; Matthews, Lynn T
Abstract : HIV transmission within stable heterosexual HIV serodiscordant couples accounts for almost half the new incident infections in South Africa and Uganda. Advances in HIV prevention provide opportunities to reduce transmission risk within serodiscordant partnerships (e.g., antiretroviral treatment (ART), pre-exposure prophylaxis (PrEP), medical male circumcision, and couples-based HIV counselling and testing). These interventions require a clinical encounter with a provider who recognises prevention opportunities within these partnerships. We explored healthcare provider understanding of HIV serodiscordance in a reproductive counselling study with providers in eThekwini district, South Africa, and Mbarara district, Uganda. In eThekwini, in-depth interviews (29) and focus group discussions (2) were conducted with 42 providers (counsellors, nurses and doctors) from public sector clinics. In Mbarara, in-depth interviews were conducted with 38 providers (medical officers, clinical officers, nurses, peer counsellors and village health workers). Thematic analysis was conducted using NVivo software. In eThekwini, many providers assumed HIV seroconcordance among client partners and had difficulty articulating how serodiscordance occurs. Mbarara providers had a better understanding of HIV serodiscordance. In the two countries, providers who understood HIV serodiscordance were better able to describe useful HIV-prevention strategies. Healthcare providers require training and support to better understand the prevalence and mechanisms of HIV serodiscordance to implement HIV-prevention strategies for HIV serodiscordant couples.